Physiological and Transcriptome Analysis of Sugar Beet Reveals Different Mechanisms of Response to Neutral Salt and Alkaline Salt Stresses - Geng, Gui; Li, Renren; Stevanato, Piergiorgio; Lv, Chunhua; Lu, Zhengyu; Yu, Lihua; Wang, Yuguang (Frontiers in Plant Science, 2020)
The salinization and alkalization of soil are widespread environmental problems. Sugar beet (B. vulgaris L.) is a moderately salt tolerant glycophyte, but little is known about the different mechanisms of sugar beet response to salt and alkaline stresses. The aim of this study was to investigate the influence of neutral salt (NaCl:Na2SO4, 1:1) and alkaline salt (Na2CO3) treatment on physiological and transcriptome changes in sugar beet. We found that a low level of neutral salt (NaCl:Na2SO4; 1:1, Na+ 25 mM) or alkaline salt (Na2CO3, Na+ 25 mM) significantly enhanced total biomass, leaf area and photosynthesis indictors in sugar beet. Under a high concentration of alkaline salt (Na2CO3, Na+ 100 mM), the growth of plants was not significantly affected compared with the control. But a high level of neutral salt (NaCl: Na2SO4; 1:1, Na+ 100 mM) significantly inhibited plant growth and photosynthesis. Furthermore, sugar beet tends to synthesize higher levels of soluble sugar and reducing sugar to cope with high neutral salt stress, and more drastic changes in indole acetic acid (IAA) and abscisic acid (ABA) contents were detected. We used next-generation RNA-Seq technique to analyze transcriptional changes under neutral salt and alkaline salt treatment in sugar beet. Overall, 4,773 and 2,251 differentially expressed genes (DEGs) were identified in leaves and roots, respectively. Kyoto encyclopedia of genes and genomes (KEGG) analysis showed that genes involving cutin, suberine and wax biosynthesis, sesquiterpenoid and triterpenoid biosynthesis and flavonoid biosynthesis had simultaneously changed expression under low neutral salt or alkaline salt, so these genes may be related to stimulating sugar beet growth in both low salt treatments. Genes enriched in monoterpenoid biosynthesis, amino acids metabolism and starch and sucrose metabolism were specifically regulated to respond to the high alkaline salt. Meanwhile, compared with high alkaline salt, high neutral salt induced the expression change of genes involved in DNA replication, and decreased the expression of genes participating in cutin, suberine and wax biosynthesis, and linoleic acid metabolism. These results indicate the presence of different mechanisms responsible for sugar beet responses to neutral salt and alkaline salt stresses.